Risiko ESG (Environmental, Social, Governance) dalam Bank Syariah : Integrasi Nilai Syariah dengan Praktik Keberlanjutan - ASYHARI, ILMA MA’RIFATUS ZUHRO (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the integration of Environmental, Social, and Governance (ESG) principles with sharia values ​​in risk management in Islamic banks. As global attention to sustainability issues increases, Islamic banks are faced with the challenge of maintaining compliance with sharia principles while adopting the ESG framework as a global standard in governance and risk management. Through a qualitative descriptive approach with literature studies and reviews of several Islamic banking practices, this study found that there is value alignment between ESG and basic sharia principles such as fairness, sustainability, and social responsibility. Environmental, social, and governance risks that arise in the operational activities of Islamic banks can be effectively mitigated through the Maqashid Sharia principles and Islamic Corporate Governance mechanisms. These findings indicate that ESG integration not only strengthens the resilience of Islamic banks to external risks but also strengthens the ethical and spiritual values ​​that are the foundation of the Islamic financial system. This study recommends strengthening regulations, increasing human resource capacity, and developing a sharia-based ESG framework as strategic steps towards more sustainable Islamic finance.